Inspiratory muscle relaxation rate assessed from sniff nasal pressure. Issue 11 (November 1994) - Kyroussis, D; Mills, G; Hamnegard, C H; Wragg, S; Road, J; Green, M; Moxham, J
Abstract : BACKGROUND--Slowing of the maximum relaxation rate (MRR) of inspiratory muscles measured from oesophageal pressure (POES) during sniffs has been used as an index of the onset and recovery of respiratory muscle fatigue. The purpose of this study was to measure MRR at the nose (PNASAL MRR), to investigate its relationship with POES MRR, and to establish whether PNASAL MRR slows with respiratory loading. METHODS--Five normal subjects were studied. Each performed sniffs before and after two minutes of maximal isocapnic ventilation (MIV). In a separate session the subjects performed submaximal sniffs. POES and PNASAL were recorded during sniffs and the MRR (% pressure fall/10 ms) for each sniff was determined. RESULTS--Before MIV mean POES MRR was 8.9 and PNASAL MRR was 9.3. The mean (SD) difference between PNASAL MRR and POES MRR during a maximal sniff was 0.48 (0.34) (n = 64) and during submaximal sniffs was 0.28 (0.46) (n = 526). The subjects showed a mean decrease in sniff POES MRR of 27.4% (range 22.5-36%) after MIV and a similar reduction in sniff PNASAL MRR of 28.5% (range 24.1-41.3%). Both returned to control values within 5-10 minutes. CONCLUSIONS--PNASAL MRR reflects POES MRR over a wide range of sniff pressures, PNASAL MRR of maximal sniffs reflects POES MRR in normal subjects at rest and following MIV, so measurement of PNASAL MRR may be a useful non-invasive method for measuring inspiratory muscle MRR, thereby providing an index of respiratory muscle fatigue.